CD1d-restricted NKT cells: regulators of inflammation and autoimmunity - Porcelli, Steven A. (Henry Stewart Talks, 2012)
Definition of NKT cells and their relation to other innate-like lymphocytes, Development of NKT cells, Mechanisms of glycolipid antigen recognition by NKT cells, Frequency and phenotype of NKT cells, Foreign and self antigens recognized, Proinflammatory functions (anti-infectious and anti-tumor activities), Anti-inflammatory and tolerance-promoting functions, Manipulation of NKT cell responses and therapeutic opportunities